Passive Warming Reduces Stress and Shifts Reproductive Effort in the Antarctic Moss, Polytrichastrum Alpinum - Zuniga-Navarro, G; Kohler-Campos, H; Casanova-Katny, A (Oxford University Press, 2017)
• Background and Aims: The Western Antarctic Peninsula is one of the most rapidly warming regions on Earth, and many biotic communities inhabiting this dynamic region are responding to these well-documented climatic shifts. Yet some of the most prevalent organisms of terrestrial Antarctica, the mosses, and their responses to warming have been relatively overlooked and understudied. In this research, the impacts of 6 years of passive warming were investigated using open top chambers (OTCs), on moss communities of Fildes Peninsula, King George Island, Antarctica. • Methods: The effects of experimental passive warming on the morphology, sexual reproductive effort and stress physiology of a common dioicous Antarctic moss, Polytrichastrum alpinum, were tested, gaining the first species-specific mechanistic insight into moss responses to warming in the Antarctic. Additionally community analyses were conducted examining the impact of warming on overall moss percentage cover and sporophyte production in intact Antarctic moss communities. • Key Results: Our results show a generally greater percentage moss cover under warming conditions as well as increased gametangia production in P. alpinum. Distinct morphological and physiological shifts in P. alpinum were found under passive warming compared with those without warming: warmed mosses reduced investment in cellular stress defences, but invested more towards primary productivity and gametangia development. • Conclusions: Taken together, results from this study of mosses under passive warming imply that in ice-free moss-dominated regions, continued climate warming will probably have profound impacts on moss biology and colonization along the Western Antarctic Peninsula. Such findings highlight the fundamental role that mosses will play in influencing the terrestrialization of a warming Antarctica. © The Author 2016. Published by Oxford University Press on behalf of the Annals of Botany Company. All rights reserved.